Al-YasÄr al-IslÄmÄ«: Iá¹lÄlah âÄmmah - AbÃ…Â« Zaid, NaÃ¡Â¹Â£r (Al-Jamiah Research Centre, 2004)
Islamic thought develop rapidly as the progress of Islam in the classical era especially when Islam facing modernity nowadays. In general, the discourse of Islamic thought ranges from the âleftâ to the ârightâ. The term